2018
DOI: 10.6007/ijarbss/v8-i9/4859
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Unemployment among Fresh Graduates: A Case Study in Klang Valley, Malaysia

Abstract: The graduate unemployment rate is one of the current issues being discussed by higher education scholars. College and university students often face unemployment after spending their valuable time and money in order to receive educational advantages. It makes them are more vulnerable to unfavourable economic conditions as those students have spent a lot of their resources while having the higher education. This paper examines the reasons and factors why fresh graduates are facing unemployment in the competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 2 publications
0
64
0
8
Order By: Relevance
“…Higher education institutions (HEI) have progressively been called upon in last years to prepare the students to work for the global world, and universities are forced to develop graduates´ employability globally (Suleman, 2017). On the other hand, the graduate unemployment is following to Hossain, Yagamaran, Afrin, Limon, Nasiruzzaman and Karim (2018) an unwelcome issue that may occur in every country around the world, and as long, the person is involved in the labour market, he or she may one day become unemployed. It is these two economic-social terms that underlie the scientific research of many authors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Higher education institutions (HEI) have progressively been called upon in last years to prepare the students to work for the global world, and universities are forced to develop graduates´ employability globally (Suleman, 2017). On the other hand, the graduate unemployment is following to Hossain, Yagamaran, Afrin, Limon, Nasiruzzaman and Karim (2018) an unwelcome issue that may occur in every country around the world, and as long, the person is involved in the labour market, he or she may one day become unemployed. It is these two economic-social terms that underlie the scientific research of many authors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the fast-paced world, changes are made rapidly, especially in the working field. Skills learnt within three to five years in tertiary education might be outdated once graduates enter the working field (Hossain et al, 2018). Due to that, employers said that graduates do not have the proper skills to work (Soulé & Warrick, 2015).…”
Section: Lack Of 21 St -Century Skillsmentioning
confidence: 99%
“…Plus, they also do not have career skills, which can be seen that most graduates are unemployed in today's world. The graduates are choosy, whereby they do not want to work in a stressful environment, so they decided to be unemployed (Hossain et al, 2018). In return, this will become a loss for the nation as youths are the main pillars for the development of the country.…”
Section: Lack Of 21 St -Century Skillsmentioning
confidence: 99%
“…Clark and Lepinteurb (2019) hypothesized that adult unemployment experience could be transmitted from older generations to analyze explained variables, namely family background, childhood, life satisfaction, and social norms. Another research applying the regression analysis model by Hossain and Afrin (2018) indicated a strong relationship between graduate attributes, employability skills, and job mismatch (Hossain et al, 2018). Considering that there have been various research papers on the Unemployment proposing regression technique, several limitations are still related to the data collection method and data input.…”
Section: Introductionmentioning
confidence: 99%